Strategic Planning and Productivity in Organizations: A Study of Selected SMEs in Anambra State - Chigbo D., Ngige (African Journal of Education,Science and Technology (AJEST), 2017)
This study analyzed strategic planning and productivity in organizations: A study of three selected SMEs in Anambra State, Nigeria. The need for an organization to proactively respond to environmental challenges was the motivating factor for the research. The objectives of the study were basically to find out the effect of strategic planning on productivity of the SMEs under study, and how and to what extent the mediating role of employee involvement and implementation incentives influences SMEs business performance. The study followed a quantitative research approach using a survey research design. The target population included all employees of the SMEs under study, which was 1, 100. A sample of 293 was drawn from the population using Taro Yamane’s formula. The reaction to the study was positive as a response rate of 98.98% (290) was obtained. The X2 (chi- square) test statistic at 0.05 level of significance was used in testing the hypotheses. The study revealed that strategic planning positively influences the productivity of the SMEs under study; and that the mediating role of employee involvement/participation and implementation incentives positively influences SMES productivity/business performance. Based on the findings, some recommendations were made which include; that the management of the SMEs are advised to adhere strictly to the processes of strategic planning, in addition to having a feedback on their strategic planning practices; so that they can position their organization to pursue growth opportunities. Moreover, managers and owners of SMEs should endeavour to make use of their employee participation and implementation incentives capabilities, which augment each other so that they would have successful business strategies.